Outcomes comparison of different surgical strategies for the management of severe aortic valve stenosis: study protocol of a prospective multicentre European registry (E-AVR registry). Issue 2 (10th February 2018) - Onorati, Francesco; Gherli, Riccardo; Mariscalco, Giovanni; Girdauskas, Evaldas; Quintana, Eduardo; Santini, Francesco; De Feo, Marisa; Sponga, Sandro; Tozzi, Piergiorgio; Bashir, Mohamad; Perrotti, Andrea; Pappalardo, Aniello; et al.
Abstract : Introduction: Traditional and transcatheter surgical treatments of severe aortic valve stenosis (SAVS) are increasing in parallel with the improved life expectancy. Recent randomised controlled trials (RCTs) reported comparable or non-inferior mortality with transcatheter treatments compared with traditional surgery. However, RCTs have the limitation of being a mirror of the predefined inclusion/exclusion criteria, without reflecting the 'real clinical world'. Technological improvements have recently allowed the development of minimally invasive surgical accesses and the use of sutureless valves, but their impact on the clinical scenario is difficult to assess because of the monocentric design of published studies and limited sample size. A prospective multicentre registry including all patients referred for a surgical treatment of SAVS (traditional, through full sternotomy; minimally invasive; or transcatheter; with both 'sutured' and 'sutureless' valves) will provide a 'real-world' picture of available results of current surgical options and will help to clarify the 'grey zones' of current guidelines. Methods and analysis: European Aortic Valve Registry is a prospective observational open registry designed to collect all data from patients admitted for SAVS, with or without coronary artery disease, in 16 cardiac surgery centres located in six countries (France, Germany, Italy, Spain, Switzerland and UK). Patients will be enrolled over a 2-year period and followed up for a minimum of 5 years to a maximum of 10 years after enrolment. Outcome definitions are concordant with Valve Academic Research Consortium-2 criteria and established guidelines. Primary outcome is 5-year all-cause mortality. Secondary outcomes aim at establishing 'early' 30-day all-cause and cardiovascular mortality, as well as major morbidity, and 'late' cardiovascular mortality, major morbidity, structural and non-structural valve complications, quality of life and echocardiographic results. Ethics and dissemination: The study protocol is approved by local ethics committees. Any formal presentation or publication of data will be considered as a joint publication by the participating physician(s) and will follow the recommendations of the International Committee of Medical Journal Editors for authorship. Trial registration number: NCT03143361 ; Pre-results.